An Analysis of the Physico-Chemical Factors and the Molecular Structure for Optimal Activity of Lipase(s) Isolated from Aspergillus Sps. - Kota Sobha (Current Topics on Chemistry and Biochemistry Vol. 4, 2022)
Extracellular lipase produced by Aspergillus japonicus was tested for its activity on sesame, groundnut and sunflower oil substrates. The enzyme showed significant activity in the pH range of 6-8 and a temperature range of 300C-400C but with sunflower oil, the activity was optimum at 500C. Of the eleven metal ions tested, only Mg2+ (2mM) enhanced the enzyme activity while others, inhibited. EDTA significantly (P <0.05) enhanced the enzyme activity suggesting that metal ions do not in general affect the lipase isolated from A. japonicus. Organic solvents and acids tested showed significant (P< 0.05) enhancement of the lipase activity at higher concentrations, presumably because of their influence on the interfacial area. Km and Vmax values of the partially purified lipase determined from Lineweaver Burk and Eadie-Hofstee plots were 63.09 (mM/L), 5.33 (mM/L/min) and 71.76 (mM/L), 5.25 (mM/L/min) respectively. Further studies included screening of fungal infestations of groundnut seeds for thermo-tolerant lipases with stability over a wide pH range and temperature, desirable for industrial applications. DNA sequencing of ITS 1, 5.8S and ITS 2 regions indicated the isolate closer to Aspergillus niger with 99% identity, and therefore designated as A. niger GN1 in this study. The pellet obtained from culture extract, subjected to 65% ammonium sulphate precipitation, was suspended in Tris-buffer and assayed for lipase activity. Two fractions of lipase (1 and 2) could be extracted at pH 4 and pH 9 respectively. Both lipase 1 and 2 fractions were characterized by LC-MS/MS spectroscopic analysis. The relative and residual activities of the enzyme fractions were high in the temperature range of 60–80 0C and over a pH of 4 & 8 for lipase 1 and 2-6 for lipase 2 fractions. LC-MS/MS confirmed the presence of Lipase 1 ( 32 kDa) and Lipase 2 ( 30 kDa) fractions with 4 and 2 unique peptides respectively.